Comparison of the quality of life of women with breast cancer after mastectomy and after breast-conserving therapy: prospective observational study - Głowacka-Mrotek, Iwona; Sowa, Magdalena; Nowacka, Krystyna; Nowikiewicz, Tomasz; Hagner, Wojciech; Zegarski, Wojciech (Journal of Medical Science, 2017)
Introduction. Breast cancer is the most common malignancy in women in developed countries. Treatment of this disease affects the quality of life of patients. Quality of life is an ambiguous concept, which refers to the state of health, severity of symptoms, and implemented treatment. It is also linked to meeting individual needs of each person. Aim. The aim of the study was to assess the quality of life of breast cancer patients according to the type of previous surgery. Material and Methods. The study was conducted prospectively. The study population included 101 women with breast cancer after surgical treatment in the period from October 2012 to October 2014 (51 cases after mastectomy, the remaining ones after breast-conserving therapy). Standard questionnaires EORTC QLQ-C30 and QLQ-BR23 were used to assess the quality of life (assessment on the day of admission to the department, two months and one year after surgery). Results. The analysis of QLQ-C30 revealed no statistically significant differences between the compared groups of patients. Regarding the analysis of QLQ-BR23, statistically significant differences related to the assessment of the patient’s own body and life perspectives, evaluation of sexual feelings and social roles (they were not found in the evaluation of sexual functioning, undesirable effects of treatment or symptoms associated with the affected breast). Conclusions. Regardless of the type of surgery performed, breast cancer patients require similar psychological actions supporting their possibility of adapting to the new situation and dealing with negative effects of surgical treatment.